2000
DOI: 10.1161/01.res.86.1.86
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Periodic Sources Underlie Ventricular Fibrillation in the Isolated Rabbit Heart

Abstract: Abstract-The mechanism(s) underlying ventricular fibrillation (VF) remain unclear. We hypothesized that at least some forms of VF are not random and that high-frequency periodic sources of activity manifest themselves as spatiotemporal periodicities, which drive VF. Twenty-four VF episodes from 8 Langendorff-perfused rabbit hearts were studied using high-resolution video imaging in conjunction with ECG recordings and spectral analysis. Sequential wavefronts that activated the ventricles in a spatially and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
136
3
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 34 publications
9
136
3
5
Order By: Relevance
“…5,6 On the other hand, type II VF is characterized by large and repeatable patterns of epicardial activations with occasional wavebreaks. These patterns of VF are consistent with those reported by Gray et al 31 and Chen et al, 32 who found significant spatiotemporal organization during fibrillation, suggesting that an ongoing focal and relatively stable source is the engine of VF. Taken together, we propose that VF associated with steep APD restitution but flat CV restitution (normal excitability) has different patterns of activation than VF associated with flat APD restitution with broad CV restitution (low excitability).…”
Section: Two Types Of Vfsupporting
confidence: 91%
“…5,6 On the other hand, type II VF is characterized by large and repeatable patterns of epicardial activations with occasional wavebreaks. These patterns of VF are consistent with those reported by Gray et al 31 and Chen et al, 32 who found significant spatiotemporal organization during fibrillation, suggesting that an ongoing focal and relatively stable source is the engine of VF. Taken together, we propose that VF associated with steep APD restitution but flat CV restitution (normal excitability) has different patterns of activation than VF associated with flat APD restitution with broad CV restitution (low excitability).…”
Section: Two Types Of Vfsupporting
confidence: 91%
“…The focal source hypothesis 4,5,27 postulates that fibrillation is maintained by a stable, rapid reentrant circuit (the "mother rotor") from which activation wavelets emanate but fail to conduct 1:1 to the surrounding tissues because of preexisting heterogeneities. Fibrillatory conduction originates wavebreak and leads to multiple wavelets, which are considered an epiphenomenon rather than the origin of fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…These wavelets can present as rotors but most commonly appear nonreentrant. 1,2 New wavelets can either arise from fragmentation of preexisting wavelets 3 or emanate from a stable rotor 4,5 according to the 2 leading hypotheses. Phase singularities (PSs) 6,7 represent sites in which the activation state cannot be determined, surrounded by a continuum of activation states ranging from fully activated to fully recovered.…”
mentioning
confidence: 99%
“…The interaction between a sustained mother rotor and underlying heterogeneity could result in conduction blocks and a complex spatial distribution of excitation frequencies, leading to VF. 2,18 …”
Section: Possible Mechanisms Of Cardiac Fibrillationmentioning
confidence: 99%
“…1 In contrast, type 2 (slow) VF is associated with a flat APD restitution, reduced excitability, and local spatiotemporal periodicity, 1 compatible with VF due to a focal source. 2 However, the nature of this focal source during type 2 VF remains unclear. We [3][4][5] previously demonstrated that the papillary muscle (PM) can serve as a site for anchoring reentry.…”
mentioning
confidence: 99%